Outcomes and relapse patterns following chemotherapy in advanced Hodgkin lymphoma in the positron emission tomography era - Lapuz C (Dove Medical Press, 2018)
Carminia Lapuz,1–3 Anoop K Enjeti,2,4 Peter C O’Brien,1,2 Anne L Capp,1,2 Elizabeth G Holliday,2,5 Sanjiv A Gupta1,2 1Department of Radiation Oncology, Calvary Mater Newcastle, Newcastle, NSW, Australia; 2Faculty of Medicine and Public Health, University of Newcastle, Newcastle, NSW, Australia; 3Department of Radiation Oncology, Olivia Newton-John Cancer Centre, Austin Health, VIC, Australia; 4Department of Haematology, Calvary Mater Newcastle, Newcastle, NSW, Australia; 5Faculty of Public Health, Hunter Medical Research Institute, Newcastle, NSW, Australia Background: This study evaluated relapse patterns and survival in advanced Hodgkin lymphoma (HL) patients treated with doxorubicin, bleomycin, vinblastine and dacarbazine (ABVD) with positron emission tomography (PET) used for staging and response assessment. Patients and methods: Patients aged 18 years or above with newly diagnosed histologically proven Stage III or IV HL treated with ABVD at Calvary Mater Newcastle from January 2005 to December 2012 were included in this study. All patients underwent pre-chemotherapy staging with 18F-fluorodeoxyglucose PET or PET/computed tomography and post-chemotherapy PET or PET/computed tomography for the assessment of response. Results: Forty-three patients were included in the study. The 5-year disease-free survival, progression-free survival and overall survival were 88%, 74% and 86%, respectively. PET complete response was seen in 35 patients (81%), and the 5-year overall survival for this group was 94%. Relapse following a PET complete response was low (three patients) and occurred predominantly at the initial sites of disease. Four of five patients with bulky disease received consolidative radiotherapy and no in-field relapses were observed. Conclusion: Advanced stage HL with a PET complete response following ABVD is associated with an excellent prognosis. Keywords: Hodgkin lymphoma, advanced, PET scan